On Classification of Semigroup N by Green’s Theorem - Suha Wazzan; Nurten Urlu Ozalan (Journal of Mathematics)
In previous papers, it has been recently defined a new class of semigroups based on both Rees matrix and completely 0-simple semigroups. For this new structure, it has been introduced with certain basic properties and finiteness conditions. The main goal of the paper is to prove Green’s Theorem for N by indicating the existence of Green’s lemma. We also study generalized Green’s relation over N and present some new findings. In particular, we classify our semigroup N associated with generalized Green’s relation by constructing good homomorphism.